Large-Scale Variation Among Human and Great Ape Genomes Determined by Array Comparative Genomic Hybridization - Locke, Devin P.; Segraves, Richard; Carbone, Lucia; Archidiacono, Nicoletta; Albertson, Donna G.; Pinkel, Daniel; Eichler, Evan E. (Genome Research, 2003)
Large-scale genomic rearrangements are a major force of evolutionary change and the ascertainment of such events between the human and great ape genomes is fundamental to a complete understanding of the genetic history and evolution of our species. Here, we present the results of an evolutionary analysis utilizing array comparative genomic hybridization (array CGH), measuring copy-number gains and losses among these species. Using an array of 2460 human bacterial artificial chromosomes (BACs) (12% of the genome), we identified a total of 63 sites of putative DNA copy-number variation between humans and the great apes (chimpanzee, bonobo, gorilla, and orangutan). Detailed molecular characterization of a subset of these sites confirmed rearrangements ranging from 40 to at least 175 kb in size. Surprisingly, the majority of variant sites differentiating great ape and human genomes were found within interstitial euchromatin. These data suggest that such large-scale events are not restricted solely to subtelomeric or pericentromeric regions, but also occur within genic regions. In addition, 5/9 of the verified variant sites localized to areas of intrachromosomal segmental duplication within the human genome. On the basis of the frequency of duplication in humans, this represents a 14-fold positional bias. In contrast to previous cytogenetic and comparative mapping studies, these results indicate extensive local repatterning of hominoid chromosomes in euchromatic regions through a duplication-driven mechanism of genome evolution.[Supplemental material is available online at www.genome.org. The following individuals kindly provided reagents, samples, or unpublished information as indicated in the paper: O. Ryder, L. Faust, and E. Adams.]
10.1101/gr.1003303